Well-Being as a Precursor and Consequence of Micro-Processes in a Group Psychotherapy With Forensic Patients - Bieg, Madeleine; Ross, Thomas; Bulla, Jan; Kluttig, Tilman; Fontao, María Isabel (Frontiers in Psychiatry, 2020)
Psychotherapy is an important approach for the treatment of psychiatric disorders. Apart from treating the disorder as such, psychotherapy aims at increasing patients’ well-being. To some extent, however, psychotherapy can be hard work and may therefore decrease patients’ subjective well-being at least in the immediate therapy situation. The Therapeutic Cycle Model (TCM; Mergenthaler, 1996) is a process-oriented theoretical model that makes assumptions about psychotherapeutic progress based on verbatim content. The model helps to identify therapeutic factors on a speech level. The present study aims at analyzing transcripts of group therapy sessions with forensic psychiatric patients using the rationale of the TCM. Furthermore, the relationship between linguistic features of psychotherapy sessions and patients’ well-being before and after therapy are investigated. In order to identify therapeutic factors, a group psychotherapy with nine drug addicted forensic psychiatric patients was videotaped and transcripts of N = 16 sessions were analyzed. Furthermore, several process-oriented measures were rated by the patients, their therapists, and an external observer. Patients’ self-reported well-being before therapy was negatively related to Connecting (indicating emotional insight) and the frequency of therapeutic cycles, which are both thought of as key moments in therapy. Well-being of forensic patients is not necessarily a helpful precursor for insightful and productive events in therapy to occur. The findings help to better understand psychotherapeutic micro-processes throughout forensic therapies, and their relationship with patients’ well-being. Implications for research and the forensic practice are discussed.